2017
DOI: 10.1016/j.puhe.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The £ for lb. Challenge . Evaluation of a novel, workplace-based peer-led weight management programme, 2014–2016

Abstract: The £ for lb. Challenge was an effective, low-cost health improvement intervention with meaningful weight loss for many participants, particularly male workers. With high levels of engagement and ownership, and successful collaboration between public health, voluntary bodies, private companies and public organisations, it is a novel workplace-based model with potential to expand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…11 Our study differed because the Wellness Champions not only offered peer support, but they were also responsible for delivering program information. In a similar study, researchers reported high program engagement and completion rates for a weight management program led by “volunteer coworker-champions.” 12 Altogether, these results suggest that Wellness Champions play an important role in the delivery and implementation of HWBI in “real-world” settings, and their fidelity to program protocols directly impact important behavioral and participant satisfaction outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…11 Our study differed because the Wellness Champions not only offered peer support, but they were also responsible for delivering program information. In a similar study, researchers reported high program engagement and completion rates for a weight management program led by “volunteer coworker-champions.” 12 Altogether, these results suggest that Wellness Champions play an important role in the delivery and implementation of HWBI in “real-world” settings, and their fidelity to program protocols directly impact important behavioral and participant satisfaction outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…The authors of this study attributed this success to participants engaging long-term in the programme; the peer-led approach may have facilitated this. Another study that evaluated the impact of a peer-led workplace weight-management intervention, based on the NHS Choices weight-loss guide, found significant weight reductions over 12 weeks, although it is not clear if the outcomes were due to the peer-led aspect or the workplace setting [ 56 ]. Shape-Up’s peer-led approach embedded in a structured behavioural programme is novel and has potential to enhance outcomes through greater engagement of participants, as trust and influence may be greater with a peer leader compared to a health professional as well as keeping delivery costs to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of home-, 119 school-, 118 and community-based 120 There is some evidence that layperson-or peer-led approaches support positive behavioral change and improved health outcomes among adults living with obesity [122][123][124][125] or obesity-related comorbidities. 126 Layperson-or community-led interventions have proved to be associated with low-resource areas or settings in which culturally tailored approaches are preferred by community members.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%